Osseodensification enables bone healing chambers with improved low-density bone site primary stability: an in vivo study - Rafael Coutinho Mello-Machado (Nature Portfolio, 2021)
Abstract Primary implant stability is a prerequisite for successful implant osseointegration. The osseodensification technique (OD) is a non-subtractive drilling technique that preserves the bone tissue, increases osteotomy wall density, and improves the primary stability. This study aimed to investigate the hypothesis that OD, through a wider osteotomy, produces healing chambers (HCs) at the implant-bone interface without impacting low-density bone primary stability. Twenty implants (3.5 × 10 mm) with a nanohydroxyapatite (nHA) surface were inserted in the ilium of ten sheep. Implant beds were prepared as follows: (i) 2.7-mm-wide using subtractive conventional drilling (SCD) technique (n = 10); (ii) 3.8-mm-wide using an OD bur system (n = 10). The sheep were randomized to two groups, with samples collected at either 14-(n = 5) or 28-days (n = 5) post-surgery and processed for histological and histomorphometric evaluation of bone-implant contact (BIC) and bone area fraction occupancy (BAFO). No significant group differences were found with respect to final insertion torque and implant stability quotient (p > 0.050). BIC values were higher for SCD after 14 and 28 days (p < 0.050); however, BAFO values were similar (p > 0.050). It was possible to conclude that the OD technique allowed a wider implant bed preparation without prejudice on primary stability and bone remodeling.